RISKS AND PROSPECTS OF INVESTMENT IN CRISIS CONDITIONS - Біла, Ірина; Атаманчук, Зорина (SWorldJournal, 2023)
This article clarifies modern problems in the investment process, factors that affect the investment capacity of investors. It was also substantiated, against the background of which crises, the shares of large companies have decreased in value over the